(untitled) (International Journal of Physiotherapy, 2025)
Background: The prevalence of Type 2 Diabetes Mellitus (T2DM) is escalating in postmenopausal women, necessitating a comprehensive exploration of effective intervention strategies. Understanding the complex interplay between menopause, diabetes, and physical activity is crucial for developing targeted, evidence-based interventions. By exploring the physiological, psychological, and metabolic responses to different forms of exercise, this review aims to delve into the existing research to see the impacts of physical activity on T2DM postmenopausal health. Methods: A comprehensive search of peer-reviewed articles, clinical trials, and observational studies on physical activity and postmenopausal women with T2DM was conducted from various databases. Relevant literature was identified and analyzed to discern patterns and key findings. Inclusion criteria focused on the latest 10 years of clinical studies published up to the present, ensuring a contemporary understanding of the subject matter. Results: Out of the identified 10 studies, four reported improved glucose regulation and metabolic health, highlighting exercise’s role in managing metabolic parameters in postmenopausal women. Three studies provided benefits in body composition overall, physical performance, and muscle strength. The other three include improved quality of life, hormonal changes, and osteoporosis prevention, showcasing the broad health impacts of exercise. Conclusion: The collective evidence from this review presents a strong argument for implementing structured exercise programs addressing various health outcomes for postmenopausal women. This review, hence, contributes to establishing the role of physical activity in maintaining a healthy lifestyle in type 2 diabetic postmenopausal women.